Migraine and premenstrual syndrome: comorbid disorders? - Melhado, Eliana Meire; Eschiapati, Túlio Ruiz; Picolo, Jéssica Bidurin; Santos, Mariana Arantes; Tahan, Guilherme Martins; Maria, Rafael Dias; Volpato-de-Matos, Ana Clara (Headache Medicine, 2021)
Introduction Headache is a common symptom among women, including during the menstrual cycle. The migraine frequency in women who present migraine associated with the menstrual period ranges from 50% to 70%. Premenstrual syndrome (PMS) is prevalent among women, affecting 80% to 90% of them throughout their lives. Objective The objectives of this study were to verify PMS prevalence and its characteristics among women who present with cephalalgia in the neurology ambulatory care unit and show the prevalence of headache and its association with PMS in the gynecology ambulatory care unit. Methods It is a descriptive and qualitative study which was carried out at Emilio Carlos Teaching Hospital in the neurology and gynecology ambulatory care units with women aged 18 to 52 years old. Eighty-seven questionnaires were distributed and self-applied throughout the year of 2018 for data collection. Each questionnaire consisted of 27 questions about the life cycle of the women and their headache episodes. The diagnostic criteria for headache and migraine from the International Headache Society were used. Criteria for PMS were met according to the quality of life questionnaire. Results In gynecology unit group, 9% of the women did not present headache, 76% had PMS and 94% presented with headache during PMS. In neurology, 79% of the women had PMS and 79% of the women who presented with cephalalgia also had PMS. Conclusion There is a large percentage of PMS in both groups, i.e. neurological unit and gynecological unit, showing it is not a spurious correlation.